A new ornithopod dinosaur (Dinosauria: Ornithischia) from the Late Cretaceous of central Patagonia - Ibiricu, Lucio Manuel; Casal, Gabriel; Martínez, Rubén Darío; Luna, Marcelo; Canale, Juan Ignacio; Álvarez, Bruno N.; González Riga, Bernardo (Cretaceous Research)
A new ornithopod dinosaur, the medium-sized Sektensaurus sanjuanboscoi gen. et sp nov. from the ConiacianeMaastricthian strata of the Lago Colhue Huapi Formation, Golfo San Jorge Basin, Patagonia, is here described. The specimen consists of disarticulated postcranial bones belonging to a single individual. It is diagnosed by an unique association of five autapomorphies on the dorsal and sacral vertebrae and the humerus. A cladistics analysis indicates that Sektensaurus was an iguanodontian ornithopod which inhabited Patagonia during the Late Cretaceous. Likewise, Sektensaurus is the first nonhadrosaurid, probably elasmarian, ornithopod recorded from the uppermost Cretaceous of central Patagonia. In a broad context, this discovery increases the anatomical knowledge of ornithopods and adds new data on the composition of dinosaur faunas that lived in Patagonia close to the Antarctica, at the end of the Cretaceous. Fil: Ibiricu, Lucio Manuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto Patagónico de Geología y Paleontología; Argentina Fil: Casal, Gabriel. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Martínez, Rubén Darío. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Luna, Marcelo. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Canale, Juan Ignacio. Provincia del Neuquén. Municipalidad de Villa El Chocón. Museo Paleontológico "Ernesto Bachmann"; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Álvarez, Bruno N. Universidad Nacional de la Patagonia Austral. Centro de Investigaciones y Transferencia Golfo San Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro de Investigaciones y Transferencia Golfo San Jorge. Universidad Nacional de la Patagonia "San Juan Bosco". Centro de Investigaciones y Transferencia Golfo San Jorge; Argentina Fil: González Riga, Bernardo. Consejo Nacional de ...